Nurses' Experiences in Caring for Older Adults With Responsive Behaviors of Dementia in Acute Care - Marie-Lee Yous RN, BScN, MScN; Jenny Ploeg RN, PhD; Sharon Kaasalainen RN, PhD; Lori Schindel Martin RN, PhD (SAGE Publishing, 2019)
Introduction: Approximately 56,000 individuals with dementia were admitted to Canadian hospitals in 2016, and 75% of them experience responsive behaviors. Responsive behaviors are words or actions used to express one's needs (e.g., wandering, yelling, hitting, and restlessness). Health-care professionals perceive these behaviors to be a challenging aspect in providing care for persons with dementia. Aims: This study explores the perceptions of nurses about (a) caring for older adults with dementia experiencing responsive behaviors in acute medical settings and (b) recommendations to improve dementia care. Methods: Thorne's interpretive description approach was used. In-person, semistructured interviews were conducted with 10 nurses and 5 allied health professionals from acute medical settings in an urban hospital in Ontario. Interviews were conducted with allied health professionals to understand their perspectives regarding care delivery for persons with responsive behaviors of dementia. Data were analyzed using Braun and Clarke's experiential thematic analysis. Findings: Themes related to caring for individuals with responsive behaviors included (a) delivering care is a complex experience, (b) using pharmacological strategies and low investment nonpharmacological strategies to support older adults with responsive behaviors, (c) acute medical settings conflicted with principles of dementia care due to a focus on acute care priorities and limited time, and (d) strong interprofessional collaboration and good continuity of care were facilitators for care. Conclusions: Findings provide guidance for improved support for nurses who provide care for individuals experiencing responsive behaviors in acute medical settings such as increasing staffing and providing educational reinforcements (e.g., annual review of dementia care education and in-services).